Earthquake effects on historical masonry buildings in Üsküdar - Temel, Orçun Nazım. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The purpose of this study is, identifying historical masonry structures in Üsküdar area and according to the known information about their history, revealing the damages occurred from the previous earthquakes. For this study, collected information from the libraries about the historical buildings in Üsküdar area and their history are summarized. From this library study, tables and graphs created showing these buildings damage reports after the previous earthquakes and how many times these buildings have been restorated because of these earthquakes. In addition to this, since the library study revealed that these masonry structures have been effected from previous earthquakes, Maiden’s Tower which is one of the best known historical building in Üsküdar area has been statically investigated according to the predicted earthquake scenarios. Furthermore, Maiden’s Tower, which has been damaged from the 1999 İzmit earthquake and restorated at 2001 by TURES firm, supplies a perfect example for restoration of a masonry structure. This thesis contains information about analysis of Maiden’s Tower before restoration condition and after restoration condition according to the architectural surveys of the structure. In this thesis Macro-Modeling analysis of Maiden’s Tower has been done by using Finite Element Methods. All in all, this thesis with its library study proves that, previous earthquakes damaged masonry structures in Üsküdar area and these structures are in at risk. Analysis of Maiden’s Tower before restoration condition showed that macro-modeling approach has given reliable results when compared to the occurred cracks at the structure after the İzmit earthquake. After restoration results showed that by restoration a masonry structure can be strengthened. This thesis also contains information about analyzing a masonry structure by using today’s analyze methods and other methods for analyzing masonry structures
Keywords: Earthquake resistant design.; Masonry.; Concrete construction -- Earthquake effects -- Turkey.; Buildings -- Earthquake effects -- Turkey.